Redescription of Parapercis rufa Randall, 2001, a replacement name for P. rosea Fourmanoir, 1985, based on specimens newly collected from southern Taiwan - Ho, Hsuan–Ching; Causse, Romain (Zootaxa, 2012)
The red sandperch Parapercis rufa Randall, 2001 is redescribed on the basis of three specimens newly collected fromTaiwan that represent the second record of the species and first record from Taiwan. The species is now redefined as aspecies of Parapercis with a large black spot with whitish rim above the pectoral-fin base, upper lobe of caudal fin witha prolongation extending about 1.0–1.5 times orbital diameter posterior to rear fin margin, and a combination of coloration and morphometric and meristic data.